The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1021/es0525253
|View full text |Cite
|
Sign up to set email alerts
|

New Orleans Soil Lead (Pb) Cleanup Using Mississippi River Alluvium:  Need, Feasibility, and Cost

Abstract: In New Orleans, LA prior to hurricane Katrina 20-30% of inner-city children had elevated blood Pb levels > or =10 microg/ dL and 10 census tracts had a median surface soil level of Pb >1000 mg/kg (2.5 times the U.S. standard). This project tests the feasibility of transporting and grading contaminated properties (n = 25) with 15 cm (6 in.) of clean Mississippi River alluvium from the Bonnet Carré Spillway (BCS) (median soil Pb content 4.7 mg/kg; range 1.7-22.8). The initial median surface soil Pb was 1051 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 46 publications
(103 reference statements)
0
33
0
Order By: Relevance
“…Zahran et al (2010) report on how natural processes did this same experiment, seeing substantially lower blood Pb levels for New Orleans children after Hurricane Katrina, due to the capping of much of the Pb-contaminated soil with flood-related sediments. Mielke et al (2006) observed that, over the course of several months after treatment, soil Pb levels in the treated sites began increasing. This increase was due to dust generated from soils from adjacent, untreated yards and neighborhoods that still had high soil Pb concentrations.…”
Section: New Views Of Lead Mitigation Approaches In Citiesmentioning
confidence: 98%
See 3 more Smart Citations
“…Zahran et al (2010) report on how natural processes did this same experiment, seeing substantially lower blood Pb levels for New Orleans children after Hurricane Katrina, due to the capping of much of the Pb-contaminated soil with flood-related sediments. Mielke et al (2006) observed that, over the course of several months after treatment, soil Pb levels in the treated sites began increasing. This increase was due to dust generated from soils from adjacent, untreated yards and neighborhoods that still had high soil Pb concentrations.…”
Section: New Views Of Lead Mitigation Approaches In Citiesmentioning
confidence: 98%
“…Most mitigation efforts for heavily-contaminated soils have involved soil removal and replacement, a disruptive and expensive option for controlling Pb sources in urban areas. Another approach was tested which was simply to cover the contaminated yard soils with about 15 cm of Pb-free soil, which in the case of New Orleans came from the nearby Mississippi levee (Mielke et al, 2006). At a fraction of the soil removal cost, this clean soil is simply graded over the old soil layer, hydroseeded, and left to grow a lawn.…”
Section: New Views Of Lead Mitigation Approaches In Citiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Capping lead contaminated urban soil with clean fill prevents contaminated soil from being resuspended as dust, thus reducing exposure through ingestion and inhalation of this resuspended soil dust, especially in summer months (Beniston and Lal, 2012;Filipelli and Laidlaw, 2010;Mielke et al, 2006;Mielke et al, 2011;Mielke et al, 2013;Wortman and Lovell, 2013). This approach is effective and financially feasible when a readily available, locally sourced fill is applied to exposed soils at the neighborhood scale (Filippelli et al, 2015).…”
Section: Introductionmentioning
confidence: 99%